2014
DOI: 10.16916/aded.99872
|View full text |Cite
|
Sign up to set email alerts
|

Ortaokul Türkçe Ders Kitaplarının Türkçe Dersi Öğretim Programındaki Temel Beceriler Açısından İncelenmesi

Abstract: Temizkan, M. (2014) Ortaokul Türkçe ders kitaplarının Türkçe dersi öğretim programındaki temel beceriler açısından incelenmesi. Ana Dili Eğitimi Dergisi Investigation of Secondary Turkish Course Books in Terms of Basic Skills in Turkish CourseCurriculum Abstract The aim of this research is to evaluate secondary Turkish coursebooks in terms of basic skills in 2005 Turkish Course Curriculum. The model applied in the study is descriptive method. The sample of this study consists of 5th, 6th, 7th and 8th grade Tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
11

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 3 publications
0
2
0
11
Order By: Relevance
“…In his study, Temizkan (2014) examined Turkish textbooks instead of curriculum and determined that these books were not sufficient to gain skills. In his study, Zevfi (2015) determined that Turkish textbooks are not sufficient in terms of reflecting basic skills and presenting these skills to students.…”
Section: Discussion Conclusion and Suggestionsmentioning
confidence: 99%
“…In his study, Temizkan (2014) examined Turkish textbooks instead of curriculum and determined that these books were not sufficient to gain skills. In his study, Zevfi (2015) determined that Turkish textbooks are not sufficient in terms of reflecting basic skills and presenting these skills to students.…”
Section: Discussion Conclusion and Suggestionsmentioning
confidence: 99%
“…Bu ihtiyaçtan dolayı okullarda bu becerinin öğretimi ve geliştirilmesi hedeflenir. Ancak alanyazındaki çalışmalara bakıldığında genel olarak ders kitaplarında eleştirel düşünme gibi becerilerin kullanılmadığı (Benzer, 2019), öğrenci çalışma kitaplarında eleştirel düşünme becerisini geliştirebilecek etkinlikler olmadığı (Dolunay ve Savaş, 2016), öğrencilerin eleştirel düşünme gücünü geliştirme konusunda yetersiz olduğu (Gün, 2012), eleştirel düşünmenin ders kitaplarında çok düzensiz bir dağılım gösterdiği (Temizkan, 2014) bulgulanmıştır. Türkçe ders kitaplarındaki etkinliklerin daha çok hatırlama, çıkarımda bulunma ve ayırt etme düşünme süreçlerini içerdiği belirlenmiştir (Bayrak Özmutlu ve Kanık Uysal, 2021).…”
Section: Tartışma Ve Sonuçunclassified
“…Games contribute to the development of communication and language skills of children, where they find opportunities of interact, share, and discuss (Aksoy, 2014;Şahhüseyinoğlu, 2007). In a study carried out in the sense of common skills in elementary curriculum, Temizkan (2014) determined that Turkish course books are not at expected level. Our analysis of IPG compilation booklet showed that "speaking Turkish correctly, effectively and fluently", skills of "speaking Turkish correctly", "writing legibly", and "speaking Turkish appropriately" are elements which were barely used in games at all grade levels that is in line with the findings of Temizkan's (2014) study.…”
Section: Problem Solvingmentioning
confidence: 99%